Adaptive sliding-mode control for robust PV power extraction under dynamic environmental conditions - Abdullahi, Salisu; Eltag, Khaled; Xiaohu, Chen; Weining, Lei; Bertilsson, Kent (Archives of Electrical Engineering, 2026)
This paper proposes a robust sliding-mode control strategy for efficient photo-voltaic (PV) energy extraction in island DC microgrids. A PV system is sensitive to voltage fluctuations. PV parameters are optimized, shunt resistance, saturation, reverse saturation, and photovoltaic current equations are modeled to maximize power generation. A boost converter increases PV output voltage to commercial levels, with the parameters carefully optimized for maximum performance. The converters are modeled using first-order differ-ential equations based on an average state-space representation, enabling the development of a sliding-mode control strategy with non-linear switching functions. The control strategy incorporates reachability dynamics to handle system non-linearities, with the control law formulated using surface switching and equivalent control. This ensures precise regulation, fast convergence, and robust performance. Validated in MATLAB/Simulink under nominal (0.6 mH) and perturbed (0.9 mH) converter inductance conditions. The results reveal: (i) fast convergence with settling times of 2.0 ms under nominal and perturbed conditions; (iii) robust performance with 8.5% overshoots (nominal) and 10.0% overshoots (perturbed), compared to 26.0% and 33.0% with conventional PID controllers. As converter inductance parameters vary, the system achieves optimal power extraction. This study shows how slid-ing-mode control can enhance PV system performance for microgrid applications.